A Study of Motor Pressure Measurement in Patients with Diabetes Mellitus - Madina Mukhammedova (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article provides information on changes in the distribution of plantar foot pressure, the incidence of side effects and complications of prophylactic footwear, and a study of the typical movement of the rear of the foot during walking. Measurements of the angular displacement of the calcaneus, scaphoid and first metatarsal relative to the tibia; the 3D motion models for all three bones were very similar. This study provides additional information on how the leg functions while walking. The results of the effectiveness of providing preventive footwear to the contingent of patients with diabetes mellitus at the Endocrinological Dispensary of the Bukhara region were analyzed (based on a sample survey and dynamic observation of 50 patients).